2008
DOI: 10.1016/j.jaut.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Extreme genetic risk for type 1A diabetes in the post-genome era

Abstract: A series of genes and loci influencing the genetic risk of type 1A (immune-mediated) diabetes are now well characterized. These include genes of the major histocompatibility complex (MHC), polymorphisms 5' of the insulin gene, and PTPN22, as well as more recently defined loci from genome-wide association studies. By far the major determinants of risk for type 1A diabetes are genes within or linked to the MHC and in particular alleles of class II genes (HLA-DR, DQ, and DP). There is evidence that MHC class I al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 61 publications
1
30
0
1
Order By: Relevance
“…In total we enrolled in the study 10 patients with a family history. this distribution is consistent with that observed in other studies in which over 85% of patients are unique cases [5]. In terms of risk for type 1 diabetes are important cases where there were first-degree relative are affected.…”
Section: Discussionsupporting
confidence: 92%
“…In total we enrolled in the study 10 patients with a family history. this distribution is consistent with that observed in other studies in which over 85% of patients are unique cases [5]. In terms of risk for type 1 diabetes are important cases where there were first-degree relative are affected.…”
Section: Discussionsupporting
confidence: 92%
“…Carriage of high risk HLA (DR3/4) and sharing of identical haplotypes with siblings has been shown to confer extreme risk of islet antibody development during childhood (16). Furthermore, testing children with high-risk HLA (17) multiple times during childhood identified individuals with multiple islet antibodies and high rate of progression to T1D (18).…”
Section: Resultsmentioning
confidence: 99%
“…9 It was later discovered that certain HLA molecules, termed DQ8 and DQ2, predispose risk for developing T1D. 10 In fact, genome-wide association studies showed that the odds ratio for developing diabetes ranged from 6.5 to 11 when either of these genes is present. 11,12 Approximately 90% of all individuals with T1D have either a DQ8 and/or a DQ2 gene, with 50-60% of all T1D patients having DQ8.…”
Section: The Trimolecular Complexmentioning
confidence: 99%